The Environment, Tourist Transport and the Sustainable Development of Tourism - Diana Ioncică; Maria Ioncică; Eva-Cristina Petrescu (Amfiteatru Economic Journal, 2016)
The article explores the complex relationships between the natural environment , tourist transport and sustainable tourism development. In order to research the impact of natural resources on tourism activity, on the one hand, and the influences of tourism on the environment, on the other hand, statistical and mathematical methods of analysis and forecast were used, namely, the analysis of the dynamics of significant indicators of the natural environment and of tourist activity, the correlation method, the Markov chains method. The analyses made lead us to the conclusion of the existence of a positive evolution of significant indicators of the natural environment, with an impact on tourist activity, such as natural parks. It has been emphasized; also, that this positive evolution has a direct influence on the attraction of visitors, specifically, foreign ones, but the intensity of this influence is average. The intensification of the actions of promotion of natural parks and, generally, of protected areas in Romania, would be a direction for attracting an increased number of visitors, with all the favourable economic consequences. On the other hand, the research has outlined the fact that, as far as the means of transportation used by tourists to visit Romania are concerned, on the first places we can see road and air transport, means of transportation which, aside from the obvious advantages for tourists, have a strong negative impact on the environment. The forecast made with the help of the Markov chains method has shown a negative trend, from the point of view of the impact on the environment, namely an increase in the share of road and air transport in the preference of foreign visitors to Romania. The current research represents a contribution to the efforts of measuring, through statistical and mathematical models, of the complex influences, in both senses, between the environment and tourist activity. Thus, an objective radiography has been made of these influences, for significant indicators of the natural environment and of tourism activity, with the aim of formulating directions of action for the increase of the positive impact and the diminishing of the negative effects.
Keywords: C53; L83; Q53; Q57; 330; the environment; tourist transport; sustainable tourism development; environmental pollution; climate change